2008
DOI: 10.1152/ajpgi.00442.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte expression of α2β1-integrin confers susceptibility to rotavirus-induced experimental biliary atresia

Abstract: lation of BALB/c mice with rhesus rotavirus (RRV) in the newborn period results in biliary epithelial cell (cholangiocyte) infection and the murine model of biliary atresia. Rotavirus infection of a cell requires attachment, which is governed in part by cell-surface expression of integrins such as ␣2␤1. We hypothesized that cholangiocytes were susceptible to RRV infection because they express ␣2␤1. RRV attachment and replication was measured in cell lines derived from cholangiocytes and hepatocytes. Flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…Thus, we tested the effect of Ha1/29 mAb directed against a2 integrin chain on IL-7-induced bone loss. The Ha1/29 mAb has shown potent blocking activity in vivo (29,30). Three-dimensional reconstructions of trabecular BV indicated that the anti-a2b1 mAb reduced trabecular bone damage associated with IL-7 treatment compared with mice treated with a control IgG mAb (Fig.…”
Section: Blockade Of A2b1 Integrin Reduces Il-7-induced Bone Loss By mentioning
confidence: 94%
“…Thus, we tested the effect of Ha1/29 mAb directed against a2 integrin chain on IL-7-induced bone loss. The Ha1/29 mAb has shown potent blocking activity in vivo (29,30). Three-dimensional reconstructions of trabecular BV indicated that the anti-a2b1 mAb reduced trabecular bone damage associated with IL-7 treatment compared with mice treated with a control IgG mAb (Fig.…”
Section: Blockade Of A2b1 Integrin Reduces Il-7-induced Bone Loss By mentioning
confidence: 94%
“…BHK21-T7 cells (baby hamster kidney cell line expressing T7 polymerase; obtained from Ursula Buchholz, NIH, Bethesda, MD) were maintained in DMEM supplemented with nonessential amino acids, L-glutamine, penicillin-streptomycin, amphotericin B, and 10% fetal calf serum. The mouse cholangiocyte cell line (mCL), generously provided by the laboratory of James Boyer (Yale Liver Care Center, Hartford, CT), was cultured as previously described (51). All media were purchased from Gibco/BRL, and cells were grown at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…MA104 cells (BioWhittaker, Walkersville, MD) were grown in Dulbecco's modified Eagle's medium (DMEM) (Cellgro) supplemented with 10% fetal bovine serum (FBS) (GIBCO BRL, Gaithersburg, MD), 0.01% penicillin-streptomycin (GIBCO BRL), 0.01% L-glutamine (GIBCO BRL), and 0.005% amphotericin B (Cellgro). The mouse cholangiocyte cell line (mCL) generously provided by the laboratory of James Boyer (Yale Liver Care Center, Hartford, CT) was cultured as described previously (12). Sixteen culture-adapted rotavirus strains were grown in MA104 cells and used in this study: NCDV, WC-3, ST-3, VA-70, DS-1, WI-61, EMcN, EB, OSU, and RRV (Monica McNeal, Cincinnati Children's Hospital Medical Center); CU-1 (ATCC, Manassas, VA): TUCH (Dr. Karol Sestak, Tulane National Primate Research Center and Tulane University School of Medicine); PA260 (Dr. Vito Matella, University of Bari Aldo Moro); GRV (Dr. Osamu Nakagomi, Nagasaki University); KU (Dr. Koki Taniguchi, Fujita Health University); and Ro1845 (Yasutaka Hoshino, National Institute of Allergy and Infectious Diseases).…”
Section: Methodsmentioning
confidence: 99%
“…Intraperitoneal injection of neonatal BALB/c mice with Rhesus rotavirus (RRV) leads to symptoms (jaundice, acholic stools, bilirubinuria) and bile duct obstruction that mimic human disease (1,18). Previous studies demonstrated the unique tropism of RRV to the cholangiocyte (biliary epithelial cells) (12,23) and that development of the murine model is virus strain dependent (1). In a previous study, it was shown that a simian rotavirus strain, SA11-FM (having a fast moving VP4 gene) induced symptoms, obstruction, and mortality whereas another similar simian strain, SA11-SM (having a different VP4 gene that was slow moving when run on a polyacrylamide gel), showed some clinical signs of hepatobiliary injury without significant mortality (1).…”
mentioning
confidence: 99%